Pola Penyakit Typhus Abdominalis di Rumah Sakit Universitas Gadjah Mada, Yogyakarta - Moefrodi W Moefrodi W (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
All patients admitted to the Department of Internal Medicine, Gadjah Mada University Hospital, Yogyakarta, with typhoid fever from January 1976 to December 1977 have been reviewed.The diagnosis was made by clinical examination and laboratory data such as Widal reaction and culture of blood, stool and urine.In that period there were 163 typhoid fever cases, 86 males and 77 females, and the average age was 22.19 years. The average duration of hospitalization was 17.6 days. All cases had fever for several days and some of them got treatment before admission. Most of the patients with chloramphenicol treatment gave excellent result.All patients who died in hospital were in bad condition. Key Words : typhoid fever - hygiene and sanitation - Salmonella - chloramphenicol resistance - rain fall